Little Red Rodent Hood - Vernon, Ursula (Hamster princess, 2018)
A little girl in a red cape asks for Princess Harriet Hamsterbone's help with a pack of weasel-wolves who want to eat her grandmother, but after meeting everyone, Harriet is not sure whom to trust.